HMI COMMUNICATION STRATEGY IN THE RECRUITMENT OF NEW MEMBERS AT THE FACULTY OF SOCIAL SCIENCES, UIN NORTH SUMATRAHMI COMMUNICATION STRATEGY IN THE RECRUITMENT OF NEW MEMBERS AT THE FACULTY OF SOCIAL SCIENCES, UIN NORTH SUMATRA - Khairul Ansor Nasution; Indira Fatra Deni (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: This study aims to determine the strategy used by the HMI FIS UINSU Commissariat in recruiting new members at the Faculty of Social Sciences and also some of the inhibiting factors. The main source or primary research data is obtained from several sources related to the member recruitment process. While the techniques used for data collection are interviews, observation and documentation. analyzed by reducing the data into a conclusion. The recruitment strategy carried out by the management of the HMI Commissariat of FIS Uinsu is CommunicationFace to Face (directly) , namely through seminars and discussions.and Media Communication (mediated communication) by utilizing print media such as pamphlets, banners and banners or social media such as creating an account facebook, instagram and whatsapp Apart from that, the HMI Commissariat FIS group also uses friendship strategies, alma mater strategies for education or Islamic boarding schools, and primordial network strategies (one area). Keywords: Communication Strategy, Islamic Student Association (HMI), Recruitment